Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4103/jehp.jehp_66_17
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method to assess compliance with ergonomic posture in dental students

Abstract: CONTEXT:The ergonomic posture protocol is extremely important for the maintenance of occupational health in dentistry. The lack of compliance with this protocol results in a high risk of developing musculoskeletal disorders.AIMS:This study developed a direct observation method for the evaluation of dental student compliance with ergonomic posture protocol.SUBJECTS AND METHODS:The method is named compliance assessment of dental ergonomic posture requirements (CADEP). During the development of the method, 14 ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 19 publications
(33 reference statements)
1
43
0
3
Order By: Relevance
“…In addition, in order to aid in this initial adaptation phase, the correct positioning of the mannequin's head based on the tooth involved in the procedure allows for adequate visualisation of the operating field and helps professionals to avoid excessive inclination of the neck and torso and consequent damages to the musculoskeletal system. 12,13,16 Another important finding in this preliminary study was that perceived difficulty of adopting the ergonomic posture items decreased significantly over the course of the school year ( According to Garcia et al, 12 the longer an inadequate posture has been established, the greater the difficulty the individual will experience when trying to correct it. Thus, the results of this study demonstrate that the implementation of ergonomic courses as part of preclinical training allows for the simultaneous development of motor skills and the posture required for safe dental procedures.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In addition, in order to aid in this initial adaptation phase, the correct positioning of the mannequin's head based on the tooth involved in the procedure allows for adequate visualisation of the operating field and helps professionals to avoid excessive inclination of the neck and torso and consequent damages to the musculoskeletal system. 12,13,16 Another important finding in this preliminary study was that perceived difficulty of adopting the ergonomic posture items decreased significantly over the course of the school year ( According to Garcia et al, 12 the longer an inadequate posture has been established, the greater the difficulty the individual will experience when trying to correct it. Thus, the results of this study demonstrate that the implementation of ergonomic courses as part of preclinical training allows for the simultaneous development of motor skills and the posture required for safe dental procedures.…”
Section: Discussionmentioning
confidence: 75%
“…4,12,13 Strategies should therefore be implemented in their academic programmes in an attempt to reduce this risk. [14][15][16][17] A strategy adopted years ago by the School of Dentistry of UNESP Araraquara is the requirement of a practical course on ergonomics in dentistry. 4,7 Despite these efforts, students were found to still have difficulty adopting the ergonomic posture taught in the ergonomics in dentistry course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalence of musculoskeletal pain is associated with the long working hours and the sedentary lifestyle of these professionals. Studies have shown that because of the ability to increase oxygen flow, improve cardiovascular/musculoskeletal function and help reduce muscle tension due to incorrect posture, these physical activities may be relevant in reducing pain symptoms in work-associated musculoskeletal disorders related to work [18][19][20][21][22] . Thus regular physical activity is suggested and is included in the curricula of undergraduate programs for the prevention of muscular disorders, especially back pain 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The rubric was developed through consultation with existing literature on correct operator and patient positioning. 6,28,29 During the bivariate analysis of the data, ethnicity was shown to be a possible confounding variable (p=0.005). A multivariate generalized linear model (GLM) was performed to assess whether ethnicity, gender, or age range were statistically significant enough to confound the relationship between the intervention and the composite score.…”
Section: Methodsmentioning
confidence: 99%